Chemistry and Biological Activities of the Genus Dalbergia - A Review - Vasudeva, Neeru; Vats, Manisha; Sharma, S.K.; Sardana, Satish (Pharmacognosy Reviews)
Dalbergia is a genus of trees, shrubs and woody climbers widely distributed in tropical and sub- tropical regions. It possesses immense traditional application. Various species are widely used as analgesic, anti-inflammatory, antipyretic, antimicrobial, antidiarrheal, anti-ulcerogenic, anti-spermicidal, larvicidal and mosquito repellant in the traditional system of medicines. Chemical investigation has resulted in characterization and isolation of various phytoconstituents. This review is compilation of chemical composition and biological activities of the various species of the genus Dalbergia.
Keywords: Biological activities; Dalbergia spp.; phytoconstituents; traditional uses